ANALISIS DATA PANEL DINAMIS PERTUMBUHAN EKONOMI DI INDONESIA DENGAN METODE FD-GMM DAN SYS-GMM - Muhammad Azis Suprayogi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2023)
Economic growth is an increase in economic activity in increasing people's income in a country for a certain period which can be measured in the form of indicators of Gross Domestic Product (GDP) at the national level and Regional Gross Domestic Product (GRDP) at the regional level. There are several factors suspected of influencing economic growth, including foreign investment, government spending, the percentage of the workforce, and the Human Development Index (IPM). This study aims to model economic growth in Indonesia using a dynamic panel data approach with the FD-GMM and SYS-GMM approaches. The data used in this study comes from the Central Bureau of Statistics in 33 provinces in Indonesia from 2011 to 2021. The results show that the variables of government spending, foreign investment, labor participation rate, and human development index have a significant influence on growth. economy in Indonesia